Public Attitude Towards Ex-Convicts’ Reintegration In Madina Township - Boateng, M.A. (University of Ghana, 2017)
In recent times recidivism rates is becoming alarming and the efforts of ensuring reintegration of ex-convicts have proven futile. The consistent failure of reintegrating ex-convicts into the communities is increasingly becoming a global concern. In the case of Ghana, issues concerning reintegration are bedeviled with numerous problems hence impeding the success story of reintegration. Most researchers have focused on the lived experiences of ex-convicts with little emphasis on public role in ensuring fruitful reintegration. Although there is paucity of research in this regard, research suggests that public attitudes towards reintegration of ex-convicts are quite ambivalent and negative. The study sought to achieve the following objectives 1. To find out the kind of attitudes that the public have towards ex-convicts in the Madina township in terms of: sex, age, educational levels and religion. 2. To identify how public attitudes are formed towards ex-convicts with regards to: religion, media and education. 3. To find the relationship between victimisation experiences and reintegration. 4. To find out the relationship between personal acquaintance and reintegration. In order to achieve these objectives, the study used a descriptive survey design. The study used a semi- structured interview schedules for data collection. Due to the unplanned and unstructured housing system within the catchment area of the study, the study employed sampling procedures which include purposive sampling, area sampling and accidental sampling techniques. A sample size of 384 respondents was chosen for the study. The major findings that emanated from the study revealed females (61.7 %) were likely to show acceptance towards ex-convict than males (38.3%).The study found out that respondents with secondary and tertiary education (75.8%) expressed readiness to accept ex-convicts more than respondents with basic education and no formal education (23.0 %). There was no significant relationship between religious affiliation and acceptability of ex-convicts as far as the study was concerned (𝑥2 =0.021 df =1 p-value = 0.884>0.05). Again, a larger percentage of the respondents (85.7%) admitted that the media have failed to educate the public enough on delicate matters of reinstating released prisoners into the society. Significantly the study also found that potential employers (41.9 %) agreed that they would offer an employment to an ex-convicts based on his or her employability, skill and knowledge of the job. The study further revealed that an overwhelming proportion of respondents (91.7%) felt threatened of ex-convicts charged with violent crimes. Finally, the study indicated that 74.7% of the respondents expressed the willingness to accept family members who are ex-convicts. Based on these findings of the study recommended that the various policy makers such as the Government of Ghana, Ghana Prison Service, Ghana Prison Ministry, the Ghana Christian Council, Ministry of Social Welfare and the Department of Adult Education and Human Resource Studies, University of Ghana should strategically formulate a mass educational policy that seek to enlighten the citizenry on reintegration.
Thesis (MPhil)
Keywords: Public Attitude; Ex-Convicts’ Reintegration; Madina Township; Ghana